Bicomplex Landau and Ikehara Theorems for the Dirichlet Series. (15th March 2022) - Agarwal, Ritu; Sharma, Urvashi Purohit; Agarwal, Ravi P.; Suthar, Daya Lal; Purohit, Sunil Dutt
Abstract : The aim of this paper is to generalize the Landau-type Tauberian theorem for the bicomplex variables. Our findings extend and improve on previous versions of the Ikehara theorem. Also boundedness result for the bicomplex version of Ikehara–Korevaar theorem is derived. The purpose of this article is to substantially extend the various complex Tauberian theorems for the Dirichlet series to the bicomplex domain.